Edaphic and topographic influence on the palm community in a montane tropical rain forest, state park of serra do mar-sp, Brazil [Influências edáfica e topográfica sobre a comunidade de palmeiras da floresta ombrófila densa montana, parque estadual da serra do mar-sp, Brasil] - Saraiva, Adriana Cristina Rosa (2016)
The work was carried out in tropical montane rain forest, situated at 23°17'-23°24' S and 45°03'-45°11' W, in order to access how the micro-environmental variations of soil, topography and litter affect the composition and structure of the palm community. In two permanent plots of one hectare, each divided into three transects (10 x 100 m) and subplots (10 x 10m), all existing palms were registered in order to determine the richness of species and the population structure. Soil samples were collected in sub plots to determine the chemical and physical properties of the soil. The thickness of the litter was determined at five random points, and the microtopography of each one was classified into ridge, slope and valley. The study recorded 3221 individuals/0.6 ha and the occurrence of four palm species: Euterpe edulis, Geonoma gamiova, G. pohliana and G. schottiana. Due to the existing relief conditions at the location, the dominant soils throughout the transects are young soils of the great Cambisol group. These soils are characterized by higher content of sand (55.00%) and silt (20.67%), minor clay (24.33%), low natural fertility evidenced by the excessive acidity (3.7), high aluminum saturation (82.3%), very low base saturation (3.9%) and also very low contents of the macronutrients Ca (2.1), Mg (1.9), K (1.1) (mmolc.dm-³) and P (4.9) (mg.dm-³). The analyses of toposequences showed that the peak position has fetility conditions slightly higher than those of the slope and valley classes. The valley class had higher sand content than the other positions. There was a slight difference in the litter layer thickness with values of 3.0 cm for the ridge, 2.5 cm for the slope and 2.3 cm for the valley position. The micro-environmental heterogeneity caused variation in the distribution and composition of only a few species of palms, especially litter layer thickness and sand concentration, which influenced the occurrence of G. gamiova seedlings and juveniles. © 2016, Institute for Environmental Research in Hydrographic Basins (IPABHi). All rights reserved.